Karakterisasi Organoleptik Dan Sifat Kimia Minuman Sari Jagung Manis (Zea Mays Saccharata L.) Kacang Tanah (Arachis Hypogaea L.) - Zainal, Zainal (Jurnal Agritechno, 2023)
Lactose intolerance is a condition where a person experiences digestive disorders because the stomach cannot digest milk sugar (lactose). The high level of public awareness of lactose intolerance makes it necessary to develop healthy milk/vegetable extracts by utilizing high protein plant foodstuffs. Therefore, the combination of sweet corn extract and peanuts is expected to increase the protein content and acceptance of these products by consumers. The purpose of this study was to analyze the effect of the comparison of sweet corn and peanuts on the organoleptic characteristics of the resulting peanut sweet corn juice drink, to determine the most preferred formulation of sweet corn and peanuts based on the level of preference of the panelists for the product by organoleptic testing, and to analyze the chemical properties of the resulting peanut sweet corn juice drink product. The method in this study was to formulate sweet corn extract products combined to peanuts with following formulations namely 30% : 0%, 20% : 10%, 15% : 15%, 10% : 20% and 0% : 30% with three repetitions and analyzed using a Completely Randomized Design (CRD). The parameters of the analysis carried out were organoleptic tests, tests for protein content, fat content, carbohydrate content, total dissolved solids, and testing the degree of acidity (pH). The results of this study indicate that based on the average organoleptic test value, the most preferred obtained was formulation A2 with a ratio of 20% sweet corn extract : 10% peanuts with a value of 3.21 (rather like). The results of the analysis of the chemical properties of the peanut sweet corn juice drink product obtained results with an average value of 1.57% protein content, 1.92% fat content, 2.58% carbohydrate content, pH 6.71 and 6oBrix total dissolved solids. The conclusion obtained in this study was that the best treatment of peanut sweet corn juice drink obtained in this study is in accordance with several parameters in the SNI for vegetable based beverage/milk products. Keywords: Sweet corn, peanuts, drink.